Feeling Exclusion Religious Conflict, Exile and Emotions in Early Modern Europe - Tarantino, Giovanni; Zika, Charles (Taylor & Francis, 2019)
Feeling Exclusion: Religious Conflict, Exile and Emotions in Early Modern Europe investigates the emotional experience of exclusion at the heart of the religious life of persecuted and exiled individuals and communities in early modern Europe. Between the late fifteenth and early eighteenth centuries an unprecedented number of people in Europe were forced to flee their native lands and live in a state of physical or internal exile as a result of religious conflict and upheaval. Drawing on new insights from history of emotions methodologies, Feeling Exclusion explores the complex relationships between communities in exile, the homelands from which they fled or were exiled, and those from whom they sought physical or psychological assistance. It examines the various coping strategies religious refugees developed to deal with their marginalization and exclusion, and investigates the strategies deployed in various media to generate feelings of exclusion through models of social difference, that questioned the loyalty, values, and trust of "others". Accessibly written, divided into three thematic parts, and enhanced by a variety of illustrations,Feeling Exclusion is perfect for students and researchers of early modern emotions and religion.